Impactos dos preços e do crédito rural sob re a produção de cana-de-açúcar no estado de São Paulo - Figueira, Sergio Rangel Fernandes [UNESP] (My University, 2020)
The objective of this study is to measure the elasticities of the sugarcane price, the price of beef (mainly the replacement of pastures by cane fields in the state), and the variation of the rural credit concession on sugarcane production, productivity and planted area in the São Paulo state. The panel data model was used for the thirty Rural Development Offices with the largest participation in sugarcane production in the state between 1995 and 2012. The results show that the price of sugarcane in four lags impacted on the production, the planted area, and productivity. The price of beef, in one and two lags, and the concession of credit, in four lags, impacted in the production and the planted area. We concluded that price expectations for decisions related to planted area and purchase of inputs to increase productivity consider past prices. The rural credit concession impacted the planted area and consequently the production. The model of production was very similar to the model for area planted with sugarcane in the state of São Paulo. Production variation was more influenced by area variation than productivity.
Keywords: beef prices; elasticities; rural credit concession; sugarcane prices; sugarcane production; São Paulo state